Passive Sampling in Regulatory Chemical Monitoring of Nonpolar Organic Compounds in the Aquatic Environment - Booij, Kees; Robinson, Craig D; Burgess, Robert M; Mayer, Philipp; Roberts, Cindy A; Ahrens, Lutz; Allan, Ian J; Brant, Jan; Jones, Lisa; Kraus, Uta R; Larsen, Martin M; Lepom, Peter; et al. (Environmental science & technology, 2016)
We reviewed compliance monitoring requirements in the European Union, the United States, and the Oslo-Paris Convention for the protection of the marine environment of the North-East Atlantic, and evaluated if these are met by passive sampling methods for nonpolar compounds. The strengths and shortcomings of passive sampling are assessed for water, sediments, and biota. Passive water sampling is a suitable technique for measuring concentrations of freely dissolved compounds. This method yields results that are incompatible with the EU's quality standard definition in terms of total concentrations in water, but this definition has little scientific basis. Insufficient quality control is a present weakness of passive sampling in water. Laboratory performance studies and the development of standardized methods are needed to improve data quality and to encourage the use of passive sampling by commercial laboratories and monitoring agencies. Successful prediction of bioaccumulation based on passive sampling is well documented for organisms at the lower trophic levels, but requires more research for higher levels. Despite the existence of several knowledge gaps, passive sampling presently is the best available technology for chemical monitoring of nonpolar organic compounds. Key issues to be addressed by scientists and environmental managers are outlined.
Keywords: chemické látky znečišťující vodu; Biota; Environmental Monitoring; Geologic Sediments; Water Pollutants, Chemical; geologické sedimenty; organické látky; společenstvo; monitorování životního prostředí; Organic Chemicals